The Impact of Cultural Values on the Effectiveness of Television Commercials with Female Sexual Appeal: A Study of Sri Lanka - Nilaweera, Upul; Wijetunga, Dinuka (My University, 2005)
Following global trends, advertisements using sexual content have grown at a rapid speed in Sri Lanka. However, in the Sri Lankan culture, public display and discussion of sexuality is not accepted. This research attempted to identify the impact of these cultural values on the effectiveness of television advertisements using female sexual content. The findings indicate that consumers have a negative opinion about such advertisements. Negative opinions were found to have an impact on the effectiveness of advertisements. Furthermore, this negative impact was found to be more significant for those who rejected the advertisement due to cultural reasons.